Evaluation of Lithium Disilicate Surface Morphology Treated with Er,Cr:YSGG and Fractional CO2 Laser - Noor Azad Mohammed*; Zainab F. Al-Bawi; Balsam saadi Abdulhameed (Iraqi Journal of Laser, 2023)
Abstract: The use of indirect, all-ceramic restorations has grown in popularity among dentists. Studies have demonstrated that for indirect ceramic restorations to be effective over time, cement and ceramic must be bonded in a stable manner. Chemical, mechanical, and laser irradiation are among the methods used to precondition ceramic surfaces in order to increase bond strength.The objective of the study: This study was performed to investigate the roughness values and surface topography of lithium disilicate glass-ceramic treated with conventional methods and different Er,Cr:YSGG, and fractional CO2 laser conditioning parameters.Material and methods: Sixty samples of lithium disilicate glass-ceramic were divided as follows: 1- (n = 10) untreated; 2- (n = 10) Hydrofluoric acid etched; 3- (n = 10) conditioned by Er,Cr: YSGG laser at (7 W, 25 Hz, 50/50% Water/Air, pulse duration 60 us, irradiation time 2 min); 4- (n = 10) conditioned by Er,Cr:YSGG laser at (5 W, 25 Hz, 50/50% Water/Air, pulse duration 60 us, irradiation time 2 min); 5- (n = 10) conditioned by fractional CO2 laser at (power 8 W, pulse duration 10 ms); 6- (n = 10) conditioned by fractional CO2 laser at (power 6 W, pulse duration 10 ms). Then evaluated by: Profilometer, and scanning electron microscopy.Results: The highest roughness values were found in CO2 laser power 8 W treated samples, followed by Er,Cr:YSGG laser power 7W treated samples. The hydrofluoric acid-etched samples showed roughness values comparable to those of CO2 laser-irradiated samples with a power of 6 W. The untreated sample showed the smoothest surface with the lowest roughness value.Conclusion: The application of Er,Cr:YSGG, fractional CO2 lasers enhances the surface roughness of lithium disilicate samples positively, showing the promised results of using these parameters in bonding procedures.